Local Open Goverment: Key Issues In Madrid, Spain - Erdayani, Rizki; afandi, syed agung; Afandi, Muslim (JPW (Jurnal Politik Walisongo), 2024)
This study aims to analyze key issues of open government in Madrid. This city is one of the members of the Open Government Partnership (OGP) selected for the Local Government Pilot Program. A qualitative approach and bibliometric analysis methods were used in this study. The data used were obtained from the Google Scholar database through Publish or Perish with four keywords: “Madrid information access”, “Madrid transparency”, “Madrid participation”, and “Madrid collaboration”. Data selection used Mendelay, while the bibliometric map was obtained using VOSviewer. This study found that there was an increasing trend in the publication of Madrid open government articles. There were 78 relevant articles and 72 topics in the last 58 years. The main topics of focus include participation, collaboration, politics, democracy, transparency, governance, and network. Meanwhile, the latest and potential topics include digital participation, innovation, development, public-private collaboration, public space, inclusion, and capability. Since its leading role in OGP, Madrid has set fourteen commitments, four of which are their current focus: improvement of the Decide Madrid platform, improvement of the transparency portal and increase of open data visualizations, broaden the spectrum of participation, and community actions for a healthy city strategy.